2014
DOI: 10.3762/bjnano.5.117
|View full text |Cite
|
Sign up to set email alerts
|

The study of surface wetting, nanobubbles and boundary slip with an applied voltage: A review

Abstract: SummaryThe drag of fluid flow at the solid–liquid interface in the micro/nanoscale is an important issue in micro/nanofluidic systems. Drag depends on the surface wetting, nanobubbles, surface charge and boundary slip. Some researchers have focused on the relationship between these interface properties. In this review, the influence of an applied voltage on the surface wettability, nanobubbles, surface charge density and slip length are discussed. The contact angle (CA) and contact angle hysteresis (CAH) of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 85 publications
4
49
0
1
Order By: Relevance
“…Furthermore, they established a mathematic model to describe this negative dependence. In addition, Jing and Bhushan [12] and Pan et al [19] experimentally studied the surface charge-dependent slip based on the atomic force microscope technique and found similar relationship between surface charge and slip as the work of Joly et al [23].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, they established a mathematic model to describe this negative dependence. In addition, Jing and Bhushan [12] and Pan et al [19] experimentally studied the surface charge-dependent slip based on the atomic force microscope technique and found similar relationship between surface charge and slip as the work of Joly et al [23].…”
Section: Introductionmentioning
confidence: 61%
“…Usually, no-slip boundary condition at the solid-liquid interface, that is, there is no relative motion between the solid and liquid at the interface is valid in macroscale. However, in the micro/nanoscale, the boundary slip, indicating a status of relative motion between the solid and liquid, at some solid-liquid interfaces cannot been neglected when analyzing the fluidic behavior [12,[17][18][19]. Considering the convective heat transfer of the fluid flow is related to the fluidic behavior, thus, the existence of surface charge and boundary slip inevitably affect the convective heat transfer of fluid flow in a micro/nanofluidic system by affecting the fluidic behavior.…”
Section: Introductionmentioning
confidence: 97%
“…wherê0 is the pressure at the outside of the fluid field near inlet or outlet,̂0 ≥ in at the inlet, and̂0 ≤ out at the outlet; t is the tangential vector to the wall. In many previous publications about pressure-driven microchannel flow [15,35,36], the pressure gradient is assumed / = −1 × 10 −6 N/m 3 . With reference to this, in this model, in is set a variable parameter ranging from 6 to 600 Pa with the step length of 6 Pa, while out = 0; in which case, / ranges from −1 × 10 5 to −1 × 10 7 N/m 3 with the step length −1 × 10 5 N/m 3 .…”
Section: Boundary Conditionmentioning
confidence: 99%
“…Researches have shown that flat, smooth, and chemically homogenous hydrophilic surfaces exhibit no or less slip [10,11]. However, if the surface is hydrophobic, there can be slip with the magnitude up to tens of nanometers [6,[12][13][14][15]. In the meanwhile, superhydrophobic surfaces, on which the contact angle exceeds 150 ∘ and the contact angle hysteresis is less than 5 ∘ , have been proved to be able to significantly amplify the magnitude of slip.…”
Section: Introductionmentioning
confidence: 99%
“…, where b is the slip length, v is the tangential velocity, and y is the axis perpendicular to the wall. At the micro or nano scale, slip lengths of various surfaces immersed in liquid have been investigated in theoretical and experimental studies [7][8][9][10][11][12][13][14][15][16][17]. For the measurement technique, Appl.…”
Section: Introductionmentioning
confidence: 99%